Genetic and epidemiological analysis of kidney function in people of sub-Saharan Africa living with HIV - (:unkn) unknown (My University, 2019)
Nearly 500 million people worldwide suffer from chronic kidney disease (CKD) and about 80% of them live in low- and middle-income countries. Paeople living with HIV (PLHIV) are at increased risk of renal disease, particularly in sub-Saharan Africa. This situation is probably related to genetic susceptibility conferred by variants of the apolipoprotein L1 gene (APOL1). These variant highly prevalent in Africa, and particularly in West Africa, have been identified as being strongly implicated in the occurrence of serious renal diseases experienced by PLHIV.The aim of this thesis was to provide data about the long-term evolution of renal function in sub-Saharan African PLHIV treated for HIV infection and assess the risk of kidney complications associated with APOL1. We analyzed the medical and genetic data of several cohorts of PLHIV followed in different health care facilities in West and Central Africa.The prevalence and incidence of CKD in the different cohorts and estimated according to the recommendations of the Kidney Disease Outcomes Quality Initiative are low to moderate and contrast with the observations made in some countries of the region with prevalence reaching 30%.The frequencies of the 2 risk variants of the APOL1 gene are also lower than expected, with only 3 to 5% of carriers of the high-risk genotype. The observation of higher frequencies in West Africa than in Central Africa is, however, confirmed.Due to the low number of carriers of the high-risk genotype and the low prevalence of CKD, we were unable to demonstrate a significant effect of APOL1 variants on the risk of kidney complications.However, our work confirms the role of other risk factors such as age, immunosuppression, hypertension and Tenofovir Disoproxil Fumarate exposure. These observations led us to evaluate the performance of a prediction score of CKD initially developed for Western PLHIV. We show that this score can be used in sub-Saharan Africa to identify people at risk
Keywords: African Research